Imperatives of innovative activity of the enterprise in conditions of economic uncertainty - M. Rybasova (Вестник Северо-Кавказского федерального университета)
The article examines the modern aspects of the innovative activity of the enterprise in conditions of uncertainty. The main problems that a modern enterprise faces when introducing innovative technologies are outlined. Consequently, one of these problems is the personnel potential of the organization. Another problem is the need to establish the location of the new equipment, for this it is necessary to analyze the entire production process. And the third problem that enterprises face when introducing innovative technologies into their activities is an incorrect assessment of the innovation potential. In the course of the study, the indicators of innovative potential for the analysis and evaluation of the innovative development of the enterprise are considered. Due to the sanctions of the United States and other states, Russian companies began to switch from foreign cloud services to Russian ones in large numbers, and the result will be able to become long-term, as it was during the pandemic.